Advances in the understanding of cluster headache. (1st February 2017) - Leone, Massimo; Proietti Cecchini, Alberto
ABSTRACT: Introduction: Cluster headache is the worst primary headache form; it occurs in paroxysmal excruciatingly severe unilateral head pain attacks usually grouped in cluster periods. The familial occurrence of the disease indicates a genetic component but a gene abnormality is yet to be disclosed. Activation of trigeminal afferents and cranial parasympathetic efferents, the so-called trigemino-parasympathetic reflex, can explain pain and accompanying oculo-facial autonomic phenomena. In particular, pain in cluster headache is attributed, at least in part, to the increased CGRP plasma levels released by activated trigeminal system. Posterior hypothalamus was hypothesized to be the cluster generator activating the trigemino-parasympathetic reflex. Efficacy of monoclonal antibodies against CRGP is under investigation in randomized clinical trials. Areas covered: This paper will focus on main findings contributing to consider cluster headache as a neurovascular disorder with an origin from within the brain. Expert commentary: Accumulated evidence with hypothalamic stimulation in cluster headache patients indicate that posterior hypothalamus terminates rather than triggers the attacks. More extensive studies on the genetics of cluster headache are necessary to disclose anomalies behind the increased familial risk of the disease. Results from ongoing clinical trials in cluster headache sufferers using monoclonal antibodies against CGRP will open soon a new era.